Research for REGI Committee – Externalities of Cohesion Policy - Alessandro Daraio; Andrea Naldini; Roman Römisch; Gessica Vella; Enrico Wolleb (The Vienna Institute for International Economic Studies (wiiw), 2019)
The study investigates the effects of Cohesion Policy (CP) which occur in a country other than the one in which CP resources were actually spent. The study estimates that macroeconomic spillovers significantly contribute to the impact of CP. Spillovers directed to EU countries represent around 9% of the total annual CP expenditure. Other spillovers to Non-EU countries are around 8% of the CP expenditure. Macro and micro spillovers together arrive at 21% of the annual CP expenditure, 67% of which is distributed among EU countries. Around 20% of the CP expenditure can trigger sectoral spillover effects in the environment, transport and higher education sectors. The analysis demonstrates that externalities reinforce EU growth and competitiveness without CP deserting its convergence objective.
Keywords: C54; C67; C68; D62; I20; O52; Q50; R50; 330; EU Cohesion Policy; spillovers; macroeconomics; higher education and research; transport; environment